Risk factors for maternal mortality associated with eclampsia presenting at a Nigerian tertiary hospital - Rabiu KA; Adewunmi AA; Ottun TA; Akinlusi FM; Adebanjo AA; Alausa TG (Dove Medical Press, 2018)
Kabiru Afolarin Rabiu,1 Adeniyi Abiodun Adewunmi,1 Tawakwalit Abimbola Ottun,1 Fatimat Motunrayo Akinlusi,1 Adewunmi Adeoye Adebanjo,2 Taiwo Ganiyat Alausa2 1Department of Obstetrics and Gynaecology, Lagos State University College of Medicine, Ikeja, Lagos State, Nigeria; 2Department of Obstetrics and Gynaecology, Lagos State University Teaching Hospital, Ikeja, Lagos State, Nigeria Background: Eclampsia remains a leading contributor to maternal mortality, particularly in developing countries, and remains a challenge even to the most experienced obstetrician. We aimed to determine the factors associated with maternal mortality in eclamptics at the Lagos State University Teaching Hospital (LASUTH), Nigeria, in order to suggest ways to prevent this avoidable tragedy. Materials and methods: Data were prospectively collected with the aid of a specially designed proforma from January 1, 2011 to December 31, 2012. Comparison was made between the patients who died (cases) and the survivors (control). Univariate and multivariate analyses were carried out using logistic regression. Results: The case fatality rate was 19.4%. Factors independently associated with mortality were as follows: period between onset of seizures to arrival in LASUTH >12 hours (adjusted OR=22.04; 95% CI=4.62–104.95; P=0.001), vaginal delivery (adjusted OR=10.96; 95% CI=2.54–47.27; P=0.0013), presence of aspiration pneumonitis (adjusted OR=7.77; 95% CI=2.37–25.46; P=0.0007), and presence of renal failure (adjusted OR=7.09; 95% CI=2.14–23.48; P=0.0014). The use of magnesium sulfate reduced the risk of mortality (adjusted OR=0.25; 95% CI=0.09–0.72; P=0.0104). Conclusion: Maternal mortality in patients with eclampsia was associated largely with preventable factors. The use of standard obstetric services, prompt referral of patients for definitive care, and the use of simplified dosing regimen of magnesium sulfate may improve its utilization and also improve maternal outcome. Keywords: maternal mortality, eclampsia, Nigeria